DIGITAL INTEGRATED DATA SERVICE MODEL FOR BANDUNG CITY SMES USING THE SIRKUIT APPLICATION - Rangga Yudha Handika; Wawan Lulus Setiawan (Musytari : Jurnal Manajemen, Akuntansi, dan Ekonomi, 2025)
Bandung City, Indonesia, holds significant economic potential due to its strategic location as a weekend getaway for local tourists from Jakarta and encompassing numerous microenterprises. This research aims to describe (1) the definition of SME and Micro Enterprise, (2) previous data collecting process, and (3) digital integrated data service model phase. The study employs a qualitative approach with descriptive analysis. Findings indicate that years by years, Bandung have never had a chance to accurately collect all the potential database of SME’s, whereas the relevant government agencies could more easily provide substantial support if such data existed. These benefits include improved administrative order, assistance in fulfilling legal requirements, and a means to measure business turnover growth throughout the mentoring process. After go through few surveys and discuccions, Finally Bandung City’s Cooperative and SME have decided to Create an integrated model for collecting the SME data digitally throughout an application named SIRKUIT.